Elafin is related to immune infiltration and could predict the poor prognosis in ovarian cancer - Lu, Weiyu; Xie, Biao; Tan, Guangqing; Dai, Wanying; Ren, Jingyi; Pervaz, Sadaf; Li, Kun; Li, Fangfang; Wang, Yingxiong; Wang, Meijiao (Frontiers in Endocrinology, 2023)
Background Ovarian cancer (OC) is the most lethal gynecologic malignancy, yet the clinical results for OC patients are still variable. Therefore, we examined how elafin expression affects the patients’ prognoses and immunotherapy responses in OC, which may facilitate treatment selection and improve prognosis. Methods The elafin mRNA expression profile was downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus. Elafin’s prognostic potential and its relationship with clinical variables were investigated using Kaplan–Meier survival curves, time-dependent receiver operating characteristic curves as well as univariate and multivariate Cox regression models. As validation, protein expression in the tumor and adjacent tissues of OC patients was investigated by using immunohistochemistry (IHC). Comprehensive analyses were then conducted to explore the correlation between immune infiltration and elafin expression. Results A higher mRNA expression of elafin was associated with an unfavorable prognosis in TCGA cohort and was validated in GSE31245 and IHC. Moreover, elafin was indicated as an independent risk factor for OC. A significantly higher protein expression of elafin was detected in the adjacent tissues of OC patients with shorter overall survival (OS). The immune-related pathways were mainly enriched in the high-elafin-mRNA-expression group. However, the mRNA expression of elafin was favorably correlated with indicators of the immune filtration and immunotherapy response, which also proved better immunotherapy outcomes. Conclusion The high elafin expression was associated with an unfavorable OS, while it also indicated better immunotherapy responses. Thus, the detection of elafin is beneficial to diagnosis and treatment selection.